Outbreak of Acute Viral Hepatitis E in Chattogram District Managed by Bangladesh Institute of Tropical Infectious Disease from April 2018 to August 2018 (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Acute Viral Uepatitis (AVH) is a common viral hepatitis occurring in developing countries like Bangladesh.  An outbreak of acute hepatitis occurred in Halishahar & adjucent areas of Chattogram city from April 2018 to August 2018.Total 76 cases of acute hepatitis got admitted & received treatment at BITID during this period.  No study has been done so far on this subject in BITID.  We present here this outbreak management. To find out the etiology, clinical course and outcome.  Materials and methods: Total 76 clinically & biochemically documented cases were screened for the hepatotropic viral marker HAV, HBV, HEV. Cases were studied in terms of epidemiological analysis to find out the cause & mode of spread, laboratory findings, outcome & management.Results: The predominant age group was (21-30) years which was 43.5%. About 66% (50/76) were male & 34 % (26/76) were female & male female ratio was 1.9:1. HEV was the most common 100% (76/76) etiological factor of acute viral hepatitis. One patient had concomitant HBV infection & no HAV infection was found. Among clinical presentations Jaundice 100% (76/76) Anorexia 63% (48/76) Nausea 63% (48/76) were predominant. About 67% (51/76) patient drank water from WASA source & 68% (52/76) patient practiced boiling water before drinking.  Most patients 33% (25/76) came from Halishahar area. 97.3% (74/76) patients were discharged after improvement with recovery, 2.6% (2/76) patient were referred to CMCH where one was due to pregnancy & other was due to acute liver failure& no death occurred.Conclusion: The acute hepatitis occurred in Chattogram district during outbreak was mostly due to HEV infection where most patients were male & most common clinical features were jaundice, anorexia & nausea. All patients got admitted in hospital & improved after treatment.JCMCTA 2020 ; 31 (2) : 145-148